Pengaruh Bi Rate dan Nilai Tukar Rupiah-USD terhadap Investasi Lq45 Di Bursa Efek Indonesia Tahun 2009 s/d Tahun 2015 - Saptoprijono, Albertus (Journal of Economics & Business UBS, 2020)
The purpose of this study for the exchange rate of Rupiah in US Dollar against the price of stocks LQ45 in Indonesia Stock Exchange either partially or simultaneously with time limitation in period of year 2009 until 2015. in this research is descriptive quantitative, that is research method done with describes in advance the condition of the research object or company under study based on facts and data available for the fact. To test the prevailing method hypothesis is multiple linear regression using the Statistical Package for Social Science (SPSS) program version 24 with the Enter method. The technique used in this study uses purpose sampling technique in which there are 20 (twenty) companies entered and registered for 14 years (fourteen) in the Indonesia Stock Exchange LQ45 index. The results showed that the data had met classically such as normal distribution data, no multicollinearity, no heteroscedasticity, and no autocorrelation. From the results of linear regression analysis can be partial and simultaneous variable Interest Rates of Bank Indonesia and Rupiah Exchange Rate in US Dollar does not affect the price of shares LQ45. Koofesien that determines the stock price-LQ45 means of 0.2% which means that the Interest Rate of Bank Indonesia and the Rupiah Exchange Rate on US Dollar gives Influence on Stock Price LQ45, while the difference is 99.8% by other variables that are not in the research.